Theranostic Attributes of Acoustic Cluster Therapy and Its Use for Enhancing the Effectiveness of Liposomal Doxorubicin Treatment of Human Triple Negative Breast Cancer in Mice - Bush, Nigel; Healey, Andrew; Shah, Anant; Box, Gary; Kirkin, Vladimir; Eccles, Sue; Sontum, Per Christian; Kotopoulis, Spiros; Kvåle, Svein; van Wamel, Annemieke; Davies, Catharina de Lange; Bamber, Jeffrey (Frontiers in Pharmacology, 2020)
Introduction: Acoustic Cluster Therapy (ACT) comprises co-administration of a formulation containing microbubble/microdroplet clusters (PS101), together with a regular medicinal drug (e.g., a chemotherapeutic) and local ultrasound (US) insonation of the targeted pathological tissue (e.g., the tumour). PS101 is confined to the vascular compartment and, when the clusters are exposed to regular diagnostic imaging US fields, the microdroplets undergo a phase-shift to produce bubbles with a median diameter of 22 µm when unconstrained by the capillary wall. In vivo these bubbles transiently lodge in the tumour’s microvasculature. Low frequency ultrasound (300 kHz) at a low mechanical index (MI=0.15) is then applied to drive oscillations of the deposited ACT bubbles to induce a range of biomechanical effects that locally enhance extravasation, distribution and uptake of the co-administered drug, significantly increasing its therapeutic efficacy. Methods: In this study we investigated the therapeutic efficacy of ACT with liposomal doxorubicin for the treatment of triple negative breast cancer using orthotopic human tumour xenografts (MDA-MB-231-luc) in athymic mice (NCr-Foxn1nu). Doxil® (6 mg/kg, i.v.) was administered at days 0 and 21, each time immediately followed by three sequential ACT (20 mL/kg PS101) treatment procedures (n = 7–10). B-mode and nonlinear ultrasound images acquired during the activation phase were correlated to the therapeutic efficacy. Results: Results show that combination with ACT induces a strong increase in the therapeutic efficacy of Doxil®, with 63 % of animals in complete, stable remission at end of study, vs. 10 % for Doxil® alone (p < 0.02). A significant positive correlation (p < 0.004) was found between B-mode contrast enhancement due to ACT activation and therapy response. These observations indicate that ACT may also be used as a theranostic agent and that ultrasound contrast enhancement during or before ACT treatment may be employed as a biomarker of therapeutic response during clinical use.